Public Opinion, Party Competition, and the European Union in Post-Communist Europe
VIII, 280 p.
Keywords: Investigating public scepticism in Eastern Europe towards the EU, this book examines how citizens' and parties' responses to integration have been affected by economic, social, institutional and historical circumstances. Focusing on the importance of normative and instrumental bases of support and opposition for integration provides great insight.